The corporation [videorecording (DVD)] - Achbar, Mark; Abbott, Jennifer; Moore, Michael, 1954 April 23-; Chomsky, Noam; Klein, Naomi, 1970-; Paul, Leonard J.; Bakan, Joel (Zeitgeist Films, 2005)
The Corporation charts the spectacular rise of the corporation as a dramatic, pervasive presence in our everyday lives. With a deft mix of humor, visual panache and seriousness, this documentary is a timely, entertaining critique of global conglomerates.